2005
DOI: 10.1038/sj.bjp.0706434
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term exposure to the new nicotinic antagonist 1,2‐bisN‐cytisinylethane upregulates nicotinic receptor subtypes of SH‐SY5Y human neuroblastoma cells

Abstract: 1 Nicotinic drug treatment can affect the expression of neuronal nicotinic acetylcholine receptors (nAChR) both in vivo and in vitro through molecular mechanisms not fully understood. The present study investigated the effect of the novel cytisine dimer 1,2-bisN-cytisinylethane (CC4) on nAChR natively expressed by SH-SY5Y neuroblastoma cells in culture. 2 CC4 lacked the agonist properties of cytisine and was a potent antagonist (IC 50 ¼ 220 nM) on nAChRs. Chronic treatment of SH-SY5Y cells with 1 mM CC4 for 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
(98 reference statements)
1
13
0
Order By: Relevance
“…In line with previous experiments (Gotti et al, 2005b), we found that approximately 10 to 15% of SC nAChRs contained the ␣3␤2* subtype, which was shown to be strongly up-regulated by nicotine in vitro (Sallette et al, 2004;Kuryatov et al, 2005;Riganti et al, 2005). In the present in vivo experiment, however, this subtype was not up-regulated in rats self-administering nicotine or treated with nicotine via MP.…”
Section: Quantitative Immunoprecipitation Of [ 3 H]epi-bound Nachrssupporting
confidence: 50%
“…In line with previous experiments (Gotti et al, 2005b), we found that approximately 10 to 15% of SC nAChRs contained the ␣3␤2* subtype, which was shown to be strongly up-regulated by nicotine in vitro (Sallette et al, 2004;Kuryatov et al, 2005;Riganti et al, 2005). In the present in vivo experiment, however, this subtype was not up-regulated in rats self-administering nicotine or treated with nicotine via MP.…”
Section: Quantitative Immunoprecipitation Of [ 3 H]epi-bound Nachrssupporting
confidence: 50%
“…In order to confirm the expression of nAChR subunits in the NSCLC cell lines at protein level, we carried out immunoprecipitation and Western blotting studies, using Abs against various nAChR subunits whose specificity was checked and is shown in Supporting Information Figure S1. The positive control was the SH‐SY5Y neuroblastoma cell line, which has high levels of receptors containing the α3, α5, α7, β2 and β4 subunits (Riganti et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Lobeline has also been found to be roughly 10 times less potent at the α7* nAChR compared to nicotine and cytisine (Houlihan et al, 2001; Miller et al, 2004), giving it advantages over nicotine and cytisine in selectivity for the α4β2 subtype. Additionally, chronic exposure of both nicotine and cytisine has been found to upregulate nAChR expression, while this effect is not observed with lobeline (Bhat et al, 1991; Riganti et al 2005). As a result, measurement of binding levels with PET experiments in subjects with long-term cytisine or nicotine exposure would be increased relative to subjects naïve to these drugs.…”
Section: Discussionmentioning
confidence: 98%